2020
DOI: 10.1016/j.compscitech.2019.107911
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure microplasma for antibacterial silver nanoparticle/chitosan nanocomposites with tailored properties

Abstract: Room temperature atmospheric pressure microplasma (APM) was deployed for the first time for the in situ synthesis of anti-bacterial silver nanoparticle/chitosan (AgNP/CS) nanocomposites. The plasma induced liquid chemistry plays a role in the in situ formation of AgNP, the size distribution of which depends on the silver salt precursor concentration. The microplasma process has also simultaneously tailored the physical properties of the composites, through molecular chain scission and formation of physically c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 63 publications
1
26
1
Order By: Relevance
“…Over the past decade, silver (Ag) compounds and silver nanoparticles (AgNPs) have garnered prominent consideration as effective antibacterial agents due to their broad spectrum of antibacterial properties against microorganisms, low bacterial resistance, and relatively low cytotoxicity toward mammalian cells [15][16][17]. Therefore, combination of Ag-based compound with HAp can be satisfactorily used as antibacterial implant material as it combines the bioactivity of HAp and bacteriostatic ability of Ag.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, silver (Ag) compounds and silver nanoparticles (AgNPs) have garnered prominent consideration as effective antibacterial agents due to their broad spectrum of antibacterial properties against microorganisms, low bacterial resistance, and relatively low cytotoxicity toward mammalian cells [15][16][17]. Therefore, combination of Ag-based compound with HAp can be satisfactorily used as antibacterial implant material as it combines the bioactivity of HAp and bacteriostatic ability of Ag.…”
Section: Introductionmentioning
confidence: 99%
“…Three peaks were observed in the high-resolution C 1s spectrum of AgNP/ChS at 287.5, 285.9 and 284.6 eV, which are characteristic signals of the O-C=O, C-N, and C-O peaks of ChS ( Carapeto et al, 2017 ; Xu et al, 2020 ), respectively ( Figure 1B ). While in the Ag3d spectrum two characteristic peaks at 373.85 and 367.60 eV, were attributed to the binding energies of Ag 3d 3/2 and Ag 3d 5/2 ( Kumar-Krishnan et al, 2015 ; Sun et al, 2020 ; Xu et al, 2020 ), respectively ( Figure 1C ). Significantly, the XPS results indicate the successful construction of AgNP/ChS nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Animal experiments showed no significant changes in electroretinography, intraocular pressure, histological, morphometric, or immunohistochemical examinations, indicating the good biocompatibility and biosafety of chitosan for ocular delivery (Santana et al, 2020). In addition, many studies have reported that the addition of precious-metal nanoparticles, such as silver, and carbon materials, such as graphene, can improve the antibacterial activity and release capacity (Shi et al, 2016;Joz Majidi et al, 2019;Asghar et al, 2020;Shah et al, 2020;Sun et al, 2020).…”
Section: Typical Ocular Polysaccharide-based Nanocarriers and Novel Design Strategiesmentioning
confidence: 99%